TRANSLATING ANIME AND ITS DIFFICULTIES (TAMADDUN NURI JURNALI, 2024)
This study examines various translation strategies employed by English and Russian translators, with a focus on their application in the localization and adaptation of multi-semiotic video-verbal texts, such as animated films. Drawing from the classifications of translation strategies by English linguist and translator P. Newmark, as well as insights from translation theorist I. S. Alekseeva's research explores eight key strategies.